Predictors of COVID-19 vaccine uptake among people who use substances: a case study in Tehran - Salah Eddin Karimi; Sina Amadi; Zahra Rampisheh; Batool Tayefi; Neda Soleimanvandiazar; Peter Higgs; Arash Tehrani-Banihashemi; Ahmad Hajebi; Marzieh Nojomi; Gelavizh Karimijavan (Substance Abuse Treatment, Prevention, and Policy, 2024)
Abstract Background Vaccination is one of the most effective ways to manage infectious disease epidemics such as Covid-19. However, the low rates of vaccination in populations at risk including people using illicit substances, hinders the effectiveness of preventive vaccines in reducing transmission. The aim of this study was to investigate the rate of Covid-19 vaccination and its related factors among people who use substances in Tehran, Iran. Methods Between July and December 2022, 386 people who use substances aged ≥ 18 years old were recruited by convenience street-based sampling in Tehran. The outcome variable in this study was self-reported completion of at least two doses of the Covid-19 vaccine. Logistic regression was used to investigate the factors related to Covid-19 vaccination. Data were analyzed using SPSS software version 20 at the 0.05 level of significance. As a measure of risk, 95% Confidence interval (CI) was used. The level of significance was considered at 0.05. Results Almost three-quarters (n = 286) of the participants reported receiving at least two doses of the Covid-19 vaccine (95% CI, 70.2–79.3). Those participants with high school diplomas were 1.17 times more likely than less educated participants to report having had 2 vaccinations (OR of 1.17, CI 95%: 1.03–1.81). Participants with a higher mean score of having a positive attitude towards Covid-19 vaccination were more likely to have received a vaccination (OR of 1.12, CI 95%: 1.08–1.17). Ethnicity was also an influential variable, people with non-Fars ethnicity were less likely to be vaccinated than those of Fars ethnicity (OR of 0.33, CI 95%: 0.13–0.81). People with higher-than-average monthly income were more likely to report vaccination than those with low monthly incomes (OR of 1.27, CI 95%: 1.09–1.8). Also, participants reporting less access to vaccination centers had a lower chance of reporting having been vaccinated than those who reported high access to vaccination centers (OR of .17, CI 95%: .08-.36). Conclusions Covid-19 vaccine uptake was found to be relatively high among people using illicit substances in this study. Higher levels of education, Fars ethnicity, higher income levels, having a positive attitude towards vaccination and access to vaccination centers were the most important predictors of Covid-19 vaccination in this study.